Effect of implementing demonstration method on students' understanding and practical skills in Milling Machining Course - Robby Eliga Putra; Eko Indrawan; Aprilla Fortuna (Researcher and Lecturer Society, 2024)
Mechanical engineering education plays a very important role in providing students with the knowledge and skills to become competent professionals in the industrialised world. This learning process involves the integration of theoretical knowledge and practical skills, and the demonstration method naturally helps to combine both aspects. The demonstration method has proved to be a promising approach to improving students' understanding and practical skills in the subject of milling machining techniques. This study aims to improve the understanding and practical skills of Mechanical Engineering Class XI students at SMK Negeri 5 Padang through the application of the demonstration method. Using a quasi-experimental research design, the results showed that the use of the demonstration method significantly improved students' understanding and skills. The evaluation by a team of validators also showed that the method was valid in terms of materials, methods and instruments. There was a difference and an increase in scores between the control class and the experimental class. In the written comprehension test, the control class scored an average of 65, while the experimental class scored an average of 80.62. In the practical skills test using the evaluation sheet, the control class achieved an average of 48.87, while the experimental class achieved an average of 74.78. This indicates a positive influence and change in the students' understanding and practical skills after implementing the demonstration method.